OSTEOLOGY AND RELATIONSHIPS OF CUMNORIA PRESTWICHII (ORNITHISCHIA: ORNITHOPODA) FROM THE LATE JURASSIC OF OXFORDSHIRE, UK. Issue 664 (2nd September 2022) - Maidment, Susannah C. R.; Chapelle, Kimberley E. J.; Bonsor, Joseph A.; Button, David; Barrett, Paul M.
ABSTRACT: The iguanodontian dinosaurs have a fossil record that extends from the Middle Jurassic to the end of the Cretaceous, by which time they had diversified to become the dominant herbivores of Laurasian ecosystems. They are historically important because fossils of British iguanodontians were among the first to be recognised as the gigantic reptiles that formed the basis for naming Dinosauria. However, the early stages of their evolution remain obscure because of a sparse fossil record, and taxonomic and systematic controversies among non-hadrosaurid iguanodontians abound. In order to shed light on the early stages of iguanodontian evolution, new discoveries and re-interpretations of historic specimens are crucial. Here, we redescribe the Late Jurassic early-branching iguanodontian Cumnoria prestwichii from the Kimmeridge Clay Formation of Oxfordshire, UK, and assess its phylogenetic position. We find that Cumnoria is distinct from the North American taxon Camptosaurus, with which it was previously synonymized, and is valid, possessing two autapomorphies of the pectoral girdle. We recover its phylogenetic position as a non-ankylopollexian iguanodontian. Cumnoria represents one of just four valid ornithopod taxa from the Jurassic of Europe.